Fostering learner autonomy in language learning in tertiary education: an intervention study of university students in Hochiminh City, Vietnam - Le, Quynh X. (2013)
Learner autonomy is widely recognised as a desirable goal in tertiary education as it is found to comply with learner-centred approaches and enable students to pursue life-long learning (Sinclair, 2000a; Ciekanski, 2007). In language teaching and learning literature, it has become the main interest of researchers and practitioners who believe that learner autonomy can enhance students’ chance for success in learning a language. A great amount of research has been done to investigate various ways to foster learner autonomy in language teaching around the world (e.g., Benson, 2001; Breeze, 2002; Chan, 2001; Cotterall, 1995; Dam, 1995; Jing, 2006; Lo, 2010; L.C.T. Nguyen and Gu, 2013). However, learner autonomy is still widely considered a ‘western’ concept and much of the research has either been conducted in a western context or based on the western view of learner autonomy (Pierson, 1996, Sinclair, 2000a; Chan, 2001). This research aimed to gain more understanding of the development of learner autonomy in English language learning among students at a private university in Hochiminh city, Vietnam. The study has revealed that the major perception of learner autonomy in this Vietnamese context relates to ‘taking the initiative’ in learning, especially in selfstudy. The type of learner autonomy, as understood and practised by students in the context of Vietnamese tertiary education, has been argued to have the characteristics of Littlewood’s (1999) reactive autonomy. This finding lends itself to the application of Sinclair’s (2000a) teacher-guided/learner-decided approach to promoting learner autonomy. In other words, an integrated learner training programme (ILTP), which gradually developed students’ capacity to take more control in the learning process by providing them with metacognitive strategies for learning management, raising their awareness of themselves as learners and of the learning context, and encouraging them to explore the English language and its learning strategies, was perceived to foster the students’ willingness and enhance their ability to take the initiative in learning and create a habit of engaging more in self-directed learning. This study has also identified certain obstacles to promoting learner autonomy in Vietnam. In particular, the exam-oriented educational context poses significant challenges to both teachers and students in their efforts to promote autonomous learning. These difficulties include time constraints and a stringent syllabus. In addition to the contextual constraints, the large power distance between teachers and students in Vietnamese culture was also suggested to be a factor in hindering learner autonomy because it results in teacher reliance and an authoritarian view of the roles of teachers in the language classroom. This cultural trait, combined with the contextual constraints, seems to discourage teachers from giving students more control in the classroom and, at the same time, inhibits students from taking such control.